Restitution Rights for Child Victims of Sexual Violence: Justice or Legal Certainty - Yulestari, Risma; Fitriah Faisal; Dewi Ratna Sari Rustam; Handrawan Handrawan; Sitti Aisah Abdullah (JUSTISI, 2025)
The purpose of this study is to analyze the fulfillment of restitution rights for child victims of sexual violence from the perspective of justice and legal certainty, as well as to examine the obstacles that prevent these rights from being optimally fulfilled in legal practice. The method used is a normative legal approach with descriptive analysis. The novelty of this research is that it emphasizes the need for judges to automatically award compensation to child victims of sexual violence, without waiting for a request from the victim, in order to achieve justice and legal certainty. The results of the study show that although the right to restitution for child victims of sexual violence is regulated in various laws and regulations, its implementation is still far from optimal. This is due to complicated application procedures, the victims' lack of knowledge about their right to restitution, and weak law enforcement, as there are no strict sanctions for law enforcement officials who neglect their duties. Restitution as a form of compensation aims to restore the condition of the victim. However, in practice, this is often ignored by judges in deciding a case, especially if there is no request from the victim. This study highlights the importance of the active role of law enforcement officials in ensuring the fulfillment of the right to restitution without having to wait for a request from the victim, as well as the need for harmonization and confirmation of sanctions in legislation in order to realize justice and legal certainty for child victims of sexual violence. The conclusion is that even though there are various laws and regulations governing restitution, the fulfillment of the right to restitution for child victims of sexual violence still faces normative and practical obstacles in Indonesia. In practice, many judges do not consistently consider the right to restitution, so that victims do not receive adequate compensation, thereby hindering their recovery process. Legal uncertainty is also caused by weak sanctions for negligent law enforcement officials, which means that victim protection depends on individuals rather than the system. The state should make restitution a fundamental legal obligation rather than merely an option to ensure justice and legal certainty for victims.